The behaviour of graphene nanoplatelates thin film for high cyclic fatigue - Salim, Mohd Azli; Omar, Ghazali; Ismail, Norhisham; Md. Saad, Adzni; Masripan, Nor Azmmi; Naroh, Azmi; Donik, Crtomir; Dai, Feng (Universiti Malaysia Perlis, 2020)
Conductive inks thin film is a composite with conductive material that can replace a conventional and rigid electronic device into one that is flexible and thin electronic device. The thin film behavior was investigated in condition when it was subjected to cyclic bending up to 5000 cycles. The goal of this study is to obtain data for developing electrical packaging with different patterns. Surface roughness, sheet resistivity and bulk resistivity of thin films were measured at every thousand bending cycle. The surface roughness decreased as the cycles increased, meanwhile the sheet and bulk resistivity increased as the cycles increased. This GnP thin film could endure high cycle stress up to 3000 cycles before it failed.